The efficacy of i‐SCAN for detecting reflux esophagitis: a prospective randomized controlled trial. Issue 2 (25th September 2012) - Kang, H. S.; Hong, S. N.; Ko, S. Y.; Kim, Y. S.; Park, H. S.; Kim, B. K.; Lee, J. H.; Kim, S. I.; Lee, T. Y.; Kim, J. H.; Lee, S. Y.; Sung, I. K.; et al.
Summary: New imaging technologies have been applied in endoscopy to improve the detection and differentiation of subtle mucosal changes using a digital contrast method. Among them, i‐SCAN technology is the most recently developed image‐enhancing technology. We investigated whether i‐SCAN could improve the detection rate of reflux esophagitis. Interobserver agreement between endoscopists was compared with conventional white light (WL) endoscopic examination. We performed a prospective randomized controlled trial. A consecutive series of 514 subjects that underwent an esophagogastroduodenoscopy for health inspection were enrolled and randomized into the i‐SCAN group ( n = 246) and WL group ( n = 268). An esophagogastroduodenoscopy with video recording was used for detecting reflux esophagitis, and reflux esophagitis were categorized by the modified Los Angeles (LA) classification. The total number of reflux esophagitis identified by WL and i‐SCAN was 58 (21.7%) and 74 (30.1%), respectively. The diagnostic yield of reflux esophagitis was significantly higher ( P = 0.034) in the i‐SCAN group (30.1%) as compared to the WL group (21.6%). Using the modified LA classification, the detection rate of minimal changes was significantly higher ( P = 0.017) in the i‐SCAN group (11.8%) as compared to the WL group (5.6%), but the detection rates of LA‐A and LA‐B were not significantly different between the two groups ( P = 0.897 and P = 0.311, respectively). After comparison of the interobserver agreement using randomly selected video clips, the i‐SCAN group showed better agreement than the WL group (Kappa value, 0.793 vs. 0.473). Compared to WL endoscopy, applying i‐SCAN in daily practice can improve the diagnostic yield of reflux esophagitis by detecting more minimal changes in the squamo‐columnar junction of the esophagus and can improve the interobserver agreement of the modified Los Angeles classification.